Games, Groups, and the Global Good - Levin, Simon A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
How do groups form, how do institutions come into being, and when do moral norms and practices emerge? This volume explores how game-theoretic approaches can be extended to consider broader questions that cross scales of organization, from individuals to cooperatives to societies. Game theory' strategic formulation of central problems in the analysis of social interactions is used to develop multi-level theories that examine the interplay between individuals and the collectives they form. The concept of cooperation is examined at a higher level than that usually addressed by game theory, especially focusing on the formation of groups and the role of social norms in maintaining their integrity, with positive and negative implications. The authors suggest that conventional analyses need to be broadened to explain how heuristics, like concepts of fairness, arise and become formalized into the ethical principles embraced by a society.
The Evolution of Cooperation at the Level of Individuals -- Evolutionary Foundations of Cooperation and Group Cohesion -- How to Evolve Cooperation -- Beyond Enlightened Self-Interest: Social Norms, Other-Regarding Preferences, and Cooperative Behavior -- Evolution, Cooperation, and Repeated Games -- Public Good Games with Incentives: The Role of Reputation -- Groups and Networks: Their Role in the Evolution of Cooperation -- Cooperation and Group Formation -- Evolution and Construction of Moral Systems -- Games, Groups, Norms, and Societies -- Evolutionary Theory and Cooperation in Everyday Life -- The Error of God: Error Management Theory, Religion, and the Evolution of Cooperation -- Moral Motivation -- Explaining Religion: Notes Toward a Research Agenda -- Cooperation and Problems of the Commons -- Building Trust to Solve Commons Dilemmas: Taking Small Steps to Test an Evolving Theory of Collective Action -- How Democracy Resolves Conflict in Difficult Games -- Two Strategic Issues in Apologizing -- Neither Self-interest Nor Self-sacrifice: The Fraternal Morality of Market Relationships.
Keywords: Political science; Evolutionary biology; Economic theory; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Political Science; Evolutionary Biology; Electronic books